2014
DOI: 10.20876/ijobed.48555
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Annotated Drawing For Improving Nigerian Secondary School Students Achievement in Genetics

Abstract: The search for ways to bring about effective teaching and learning of biology in secondary schools has provided the impetus for this study. Therefore, the study investigated the effect of annotated drawing on the understanding of genetics by secondary school biology students. 110 secondary school students drawn from two intact classes constituted the sample for the study. Quantitative and qualitative methods were used to collect data using the research questions raised and hypotheses formulated for the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…A lot has been written to show the indispensable role of materials in curricular implementation (Onyejemezi,[7], Ogunranti, [8], Afolaju, [9]). These authors points out that instructional materials increase the rate of learning; save the teacher time and effort, increase learners interest and facilitate retention of what is learned.…”
Section: Introductionmentioning
confidence: 99%
“…A lot has been written to show the indispensable role of materials in curricular implementation (Onyejemezi,[7], Ogunranti, [8], Afolaju, [9]). These authors points out that instructional materials increase the rate of learning; save the teacher time and effort, increase learners interest and facilitate retention of what is learned.…”
Section: Introductionmentioning
confidence: 99%
“…Results of hypothesis two analysis revealed that there is no significant difference between non-projected visual and management of elementary education. This finding is germane to Danmole and Lameed (2017) that non-projected visual bring learners face to face with world so as to achieve educational goals. This finding agreed with Onasanya and Omosewo (2011) that use of nonprojected visual improved students understanding and led to high academic achievement.…”
Section: Hypotheses Testingmentioning
confidence: 97%
“…Sanders (2009) advocated that STEM education should include the objectives of at least one STEM subject, suggesting a science or mathematics learning objective in engineering or technology as an instructional medium and thus, the present study considered genetics as the science instructional content. Recent developments in the field of genetics, such as genetically modified organisms and cloning, have raised fundamental educational, ethical and financial questions and thus, the present generation of students need to equip themselves with a comprehensive understanding of genetics (Danmole & Lameed, 2014). However, the literature has revealed that teachers and students experience difficulties in teaching and learning genetics (Agboghoroma & Oyovwi, 2015;Atilla, 2012;Williams, Montgomery, & Manokore, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, learning of genetics from a traditional approach, as observed in many classrooms, could have contributed to these learning difficulties. Based on these findings, students' achievement in science (genetics) continues to be unacceptable (Danmole & Lameed, 2014). Accordingly, because of its multidisciplinary nature, the ISTEMA could provide an efficient way to study genetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation